Examining the authority and authority of judges in terms of independence, science and ijtihad in jurisprudence and law - Mahdavi, Alireza (2021)
One of the reasons that makes the position of the judiciary valuable is the issue of the implementation of Islamic justice, which we can only achieve by having fair judges with the condition of judicial independence; And this issue is one of the important goals of this research and is of special importance in the current era; And it doubles the need for our attention and research. According to the subject of the research, the method of collecting materials is documentary and library method in such a way that first the desired sources are studied and where necessary, research is done on the material. The research method is descriptive-analytical. First, the required resources are selected from electronic libraries, articles and dissertations, and after studying and separating the required material, based on the inductive method, analytical and necessary filing of the required resources is completed and compiled. This research tries to answer the question: what is the jurisprudential and legal study of the independence, science and ijtihad of judges? And what are the legal jurisprudential bases of judges' independence? What we have reached about the nature of the judge's knowledge in this study is that the expressions in Articles 211 and 212 of the Islamic Penal Code of 1392 indicate that from the legislative point of view, what is the basis for producing knowledge for the judge is evidence and the UAE typically The science is the result of judicial research. Also, the results of the research showed that the expressions in Articles 211 and 212 of the Islamic Penal Code of 1392 indicate that from the legislator's point of view, what is the basis for producing knowledge for the judge is evidence and the UAE is typically knowledgeable as a result of judicial investigation. In the current laws and procedures of the judiciary, the mujtahid of a judge is not considered a necessary condition for holding the position of judge.